2009
DOI: 10.1523/jneurosci.4341-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Probabilistic Category Learning in Patients with Schizophrenia

Abstract: Functional neuroimaging studies of probabilistic category learning in healthy adults report activation of cortical-striatal circuitry. Based on previous findings of normal learning rate concurrent with an overall performance deficit in patients with schizophrenia, we hypothesized that relative to healthy adults, patients with schizophrenia would display preserved caudate nucleus and abnormal prefrontal cortex activation during probabilistic category learning. Forty patients with schizophrenia receiving antipsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 58 publications
(75 reference statements)
9
74
1
Order By: Relevance
“…However, these differences were apparent throughout the course of the task and did not vary as a function of learning rate or time on task, raising questions as to the specific processes that they reflected. 146 In a related study, Koch et al 138 found reduced activation among individuals with schizophrenia in DLPFC and ACC in a probabilistic learning paradigm when the predictability of reward outcomes was low. Furthermore, these researchers also found reduced positive prediction error responses in frontal cortex, cingulate, and putamen.…”
Section: Reward Prediction and Wanting In Schizophreniamentioning
confidence: 98%
See 2 more Smart Citations
“…However, these differences were apparent throughout the course of the task and did not vary as a function of learning rate or time on task, raising questions as to the specific processes that they reflected. 146 In a related study, Koch et al 138 found reduced activation among individuals with schizophrenia in DLPFC and ACC in a probabilistic learning paradigm when the predictability of reward outcomes was low. Furthermore, these researchers also found reduced positive prediction error responses in frontal cortex, cingulate, and putamen.…”
Section: Reward Prediction and Wanting In Schizophreniamentioning
confidence: 98%
“…Weickert et al 146 found that controls showed greater activation than individuals with schizophrenia in both DLPFC and caudate. This was true even when analyses were restricted to a subset of controls and patients considered to be good learners.…”
Section: Reward Prediction and Wanting In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evidence suggests surprisingly intact performance on a range of tasks in which learning is either relatively easy or relatively implicit (Elliott et al 1995;Hutton et al 1998;Joyce et al 2002;Turner et al 2004;Tyson et al 2004;Jazbec et al 2007;Waltz and Gold 2007;Ceaser et al 2008;Heerey et al 2008;Weiler et al 2009;Somlai et al 2011), though with some exceptions (Oades 1997;Pantelis et al 1999). Further, individuals with schizophrenia show intact learning rates on the weather prediction task, a probabilistic category-learning task frequently used to measure reinforcement learning, though with overall impaired performance (Keri et al 2000(Keri et al , 2005aWeickert et al 2002Weickert et al , 2009Beninger et al 2003). There is some evidence that reinforcement learning may be more intact for patients on atypical than typical antipsychotics, though it has been found in those on typicals as well (Beninger et al 2003;Keri et al 2005a, b).…”
Section: Reinforcement Learningmentioning
confidence: 99%
“…34 Other authors assessing patients with schizophrenia also found differential activation patterns in frontal-striatal-thalamic regions during probabilistic learning or reward prediction tasks. [35][36][37] Imaging techniques in general might be able to unravel the neurobiological alteration during ARMS. In a review, Wood and colleagues 38 concluded that an activation of the stress system and an increased striatal dopamine synthesis seem to be a marker of ARMS patients most at risk for later transition to psychosis, but huge variations in methodology must be noted.…”
Section: J Psychiatry Neurosci 2015;40(3)mentioning
confidence: 99%